Impact Of Customer Touch Point Management On Banks’ Performance - Agu, Agu Godswill; Samuel, G. Etuk; Ikenna, Madumere Humphrey (Archives of Business Research, 2019)
The study aimed at assessing the impact of effective customer touch point management on the performance (profitability, patronage level, market share and image) of commercial banks and on customers’ satisfaction. The cross-sectional survey research design was adopted while a sample size of 130 respondents made up of First and Zenith Banks Staff and customers in Owerri Metropolis was used. Stated hypotheses were tested using the Chi-square. It was discovered among others that most customer touchpoint management strategies in commercial banks in Owerri were still ineffective and inefficient and that effective customer touchpoint management has significant impact on banks’ performance and customers’ satisfaction. The study recommended among others that commercial banks should identify and effectively manage the basic customer touchpoints and conduct periodic marketing research to assess customers’ view of the efficiency and effectiveness of their touchpoints management efforts.